Peran Permainan Edukatif Pada Perkembangan Fisik Motorik Anak Usia Dini Di Tk Aba: The Role of Educational Games in Early Childhood Physical Motor Development at Tk Aba - Zahra, Afifah; Depalina Siregar, syamsiah (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2024)
This study aims to explore the role of educational games in the physical motor development of early childhood in ABA kindergarten. The research method used is qualitative research with a case study approach. Data were collected through participatory observation, in-depth interviews with teachers and parents, and document analysis related to the educational games curriculum at ABA Kindergarten. The results showed that educational games play an important role in improving early childhood physical and motor development. By providing a supportive environment and specially designed games, ABA kindergartens succeed in creating situations that stimulate children's physical motor development. Factors such as the diversity of play, the use of appropriate play tools, and the role of teachers in directing play activities also play a vital role in achieving positive outcomes. The findings emphasize the importance of supporting physical motor development through an educational play approach in ABA kindergartens. The practical implications of this study can assist kindergarten managers and teachers in designing play activities that suit the physical motor development needs of early childhood.